Occupational exposure to fungi and particles in animal feed industry - Viegas, Carla (2018)
Background: Very few studies regarding fungal and particulate matter (PM) exposure in feed industry have been reported, although such contaminants are likely to be a significant contributing factor to several symptoms reported among workers. The purpose of this study has been to characterize fungal and dust exposure in one Portuguese feed industry. Material and Methods: Air and surface samples were collected and subject to further macro- and microscopic observations. In addition we collected other air samples in order to perform real-time quantitative polymerase chain reaction (PCR) amplification of genes from Aspergillus fumigatus and Aspergillus flavus complexes as well as Stachybotrys chartarum. Additionally, two exposure metrics were considered – particle mass concentration (PMC), measured in 5 different sizes (PM0.5, PM1, PM2.5, PM5, PM10), and particle number concentration (PNC) based on results given in 6 different sizes in terms of diameter (0.3 μm, 0.5 μm, 1 μm, 2.5 μm, 5 μm and 10 μm). Results: Species from the Aspergillus fumigatus complex were the most abundant in air (46.6%) and in surfaces, Penicillium genus was the most frequently found (32%). The only DNA was detected from A. fumigatus complex. The most prevalent in dust samples were smaller particles which may reach deep into the respiratory system and trigger not only local effects but also the systemic ones. Conclusions: Future research work must be developed aiming at assessing the real health effects of these co-exposures.